2019
DOI: 10.1111/jne.12727
|View full text |Cite
|
Sign up to set email alerts
|

Development of the basal hypothalamus through anisotropic growth

Abstract: The adult hypothalamus is subdivided into distinct domains: pre‐optic, anterior, tuberal and mammillary. Each domain harbours an array of neurones that act together to regulate homeostasis. The embryonic origins and the development of hypothalamic neurones, however, remain enigmatic. Here, we summarise recent studies in model organisms that challenge current views of hypothalamic development, which traditionally have attempted to map adult domains to correspondingly located embryonic domains. Instead, new stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Placzek and Briscoe ( 2005 ), Manning et al ( 2006 ), Fu et al ( 2019 ) and Placzek et al ( 2020 ) misinterpreted in our opinion Shh -expressing cells observed in midsagittal sections at the chicken rostral diencephalic ventral midline as an “anterior floor plate” (no doubt assuming wrongly that Shh is always a floor plate marker). Actually, these median cells correspond to the Shh -expressing basal acroterminal subdomain.…”
Section: The Hypothalamus In the Updated Prosomeric Modelmentioning
confidence: 82%
See 2 more Smart Citations
“…Placzek and Briscoe ( 2005 ), Manning et al ( 2006 ), Fu et al ( 2019 ) and Placzek et al ( 2020 ) misinterpreted in our opinion Shh -expressing cells observed in midsagittal sections at the chicken rostral diencephalic ventral midline as an “anterior floor plate” (no doubt assuming wrongly that Shh is always a floor plate marker). Actually, these median cells correspond to the Shh -expressing basal acroterminal subdomain.…”
Section: The Hypothalamus In the Updated Prosomeric Modelmentioning
confidence: 82%
“…Actually, these median cells correspond to the Shh -expressing basal acroterminal subdomain. Placzek and collaborators (Fu et al, 2019 ; Placzek et al, 2020 ) seem to have assimilated this particular notion, but conjecture a mixture of columnar and prosomeric notions in the form of a novel “anisotropic model of basal hypothalamic development.” Why the model should attend only to basal development remains unclear. In general, these authors seem to imagine the whole hypothalamus as represented by its midline.…”
Section: The Hypothalamus In the Updated Prosomeric Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The zebrafish PRR exhibits a high degree of continuous neurogenesis (Grandel et al, 2006;Wang et al, 2012). This might cause the overgrowth of the tuberal PRR and the peculiar shape of the RTuV/TuV domain which could be explained through anisotropic growth (Fu et al, 2019) of tuberal regions as the PRR bulges outward. To account for its divergent phylogenetic status, we suggest for this brain region not to adopt the mammalian nomenclature but to refer to it as PRR.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, only recently has there been a clearer understanding of how Shh governs the development and growth of the hypothalamus. It has now been shown that, after acting as a morphogen to pattern the DV axis, Shh-expressing ventral hypothalamic progenitors produce progenitors that populate much of the basal hypothalamus through anisotropic growth [ 49 ] (reviewed in [ 88 ]). The key insight from this work is that hypothalamic progenitor cells concurrently specify as they grow and migrate anisotropically.…”
Section: Discussionmentioning
confidence: 99%